Menstrual Suppression Practice among Female Malaysian Pilgrims - MR, Rafidah; H, Zuhra; S, Harlina Halizah; AS , Azah; CE, Tan (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Performing the Hajj or pilgrimage is obligatory for all Muslims. Certain Hajj religious rites cannot be performed during menstruation. Hence, it is common for female pilgrims to seek a doctor’s advice on methods of menstrual suppression during Hajj. This exploratory study aimed to determine the prevalence and usage profile of menstrual suppression practices among Malaysian women performing Hajj and their associated factors. MATERIALS AND METHODS: An observational cohort study involved 437 women aged 18-55 years old who attended compulsory pre-Hajj courses in Klang Valley, Malaysia. The self-administered questionnaires contained sociodemographic information, and biomedical characteristics were obtained. A follow-up call was made after their return from Hajj to obtain information regarding practice, medication is taken, and their intended duration of menstrual suppression. Descriptive and inferential analysis were done. RESULTS: Post Hajj, about 81.3% (347/437) of women were contactable and completed their menstrual calendar and 17.6% (62/347) of female pilgrims practiced menstrual suppression. The mean duration of hajj was 44 days and 77.4% (48/61) intended to suppress their menstruation throughout the whole of their Hajj travel. Previous use of contraception was associated with menstrual suppression practice (p<0.001). The commonest method of menstrual suppression was combined oral contraceptive pills (53.2%) followed by oral progestogens only pill (35.5%). CONCLUSION: Almost one-fifth of Malaysian female Hajj pilgrims practiced menstrual suppression. Previous use of contraception was associated with menstrual suppression practice. Combined oral contraceptive pills were the commonest method used and the method was chosen was based on the individual desired duration of menstrual suppression. ><0.001). The commonest method of menstrual suppression was combined oral contraceptive pills (53.2%) followed by oral progestogens only pill (35.5%). CONCLUSION: Almost one-fifth of Malaysian female Hajj pilgrims practiced menstrual suppression. Previous use of contraception was associated with menstrual suppression practice. Combined oral contraceptive pills were the commonest method used and the method was chosen was based on the individual desired duration of menstrual suppression.